Hermeneutical Trajectories of the Hemorrhaging Woman (Mark 5:25–34) (Journal for the Study of Religion and History (JSRH), 2026)
This study traces the hermeneutical trajectory of the healing of the hemorrhaging woman (Mark 5:25–34) to illuminate how changing interpretive frameworks have shaped understanding of Markan miracles. It then undertakes a socio-rhetorical interpretation of the narrative to offer a contemporary understanding of the text. Historically, this narrative was read apologetically, foregrounding the miracle as proof of Jesus’s divinity and a model for the efficacy of faith. The form-critical shift reclassified it as a Novelle, prioritizing its Sitz im Leben for early community instruction and Christological confession. Contemporary scholarship, however, engages its literary artistry, particularly its function as a theological intercalation within the Jairus narrative. This hermeneutical trajectory reveals a critical development within the interpretation of Markan miracles in that they are no longer seen merely as a display of power but as sophisticated rhetorical devices. Hence, the narrative is a vehicle designed to draw vulnerable persons to Jesus and to demonstrate that the power of Jesus to heal is above his peers.
Keywords: Mark 5:25–34, hermeneutics, miracles, vulnerability, rhetoric, illness, faith